Encapsulation of Berberine in Nano-Sized PLGA Synthesized by Emulsification Method. (17th September 2012) - Khemani, Manisha; Sharon, Maheshwar; Sharon, Madhuri
Abstract : Nanoparticles of PLGA (polylactide glycolic acid) were prepared using biodegradable poly (D, L-lactide-co-glycolide)—75 : 25, by emulsification method using PVA (Mol. Wt. 9000) or didodecyl dimethyl ammonium bromide (DMAB) as surfactant. Nanoparticles were morphologically characterized using scanning electron microscope (SEM) and particle size analyzer. The distribution of size of PLGA nanoparticles was in the range of 48–211 nm. Berberine, a yellow isoquinoline alkaloid that is used as traditional anticancer drug, was loaded on to PLGA nanoparticles by single emulsion as well as multiple emulsion solvent evaporation techniques. Particle size analysis showed an increase in berberine loaded PLGA NP size to 180–310 nm when PVA was used as a stabilizer. Whereas use of DMAB as a stabilizer led to precipitation. In vitro drug release analysis revealed that acidic pH of 5.5 was more suitable for release of berberine than pH 7.4.